Exploring Teachers’ Strategies in Addressing the Learning Needs of Introvert and Extrovert Students - Nurhikmah; Zul Astri; Nashruddin; Nuraeni (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
This study aimed to explore the strategies of English teachers at MTsN 1 Maros in accommodating the learning needs of introvert and extrovert students, focusing on Hamruni's (2009) theory. This research uses a qualitative approach with five English teachers from MTsN 1 Maros as participants. Semi-structured interviews were used to collect the data and the data were analyzed using thematic analysis. The results show that teachers applied direct, indirect, interactive, and independent strategies for introverts, while direct and interactive strategies suited extroverts, and for both personalities they integrated interactive, indirect, experimental, and independent strategies. These findings highlight that adaptive teaching can help increase learning engagement among students with different personalities, while reinforcing Hamruni's theory through practical application in diverse classrooms.